Effects of stratified active layers on high-altitude permafrost warming: a case study on the Qinghai-Tibet Plateau - Pan, Xicai; Li, Yanping; Yu, Qihao; Shi, Xiaogang; Yang, Daqing; Roth, Kurt (The Cryosphere, 2016)
Abstract. Seasonally variable thermal conductivity in active layers is one important factor that controls the thermal state of permafrost. The common assumption is that this conductivity is considerably lower in the thawed than in the frozen state, λt/λf < 1. Using a 9-year dataset from the Qinghai-Tibet Plateau (QTP) in conjunction with the GEOtop model, we demonstrate that the ratio λt/λf may approach or even exceed 1. This can happen in thick (> 1.5 m) active layers with strong seasonal total water content changes in the regions with summer-monsoon-dominated precipitation pattern. The conductivity ratio can be further increased by typical soil architectures that may lead to a dry interlayer. The unique pattern of soil hydraulic and thermal dynamics in the active layer can be one important contributor for the rapid permafrost warming at the study site. These findings suggest that, given the increase in air temperature and precipitation, soil hydraulic properties, particularly soil architecture in those thick active layers must be properly taken into account in permafrost models.
Gesehen am 27.10.2020